2022
DOI: 10.1016/j.lanwpc.2021.100337
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a psychiatric intervention at community level for people who inject drugs in a low-middle income country: the DRIVE-Mind cohort study in Hai Phong, Viet Nam

Abstract: Background Access to psychiatric care for people who inject drugs (PWID) is limited/absent and stigmatized in most low-middle-income countries (LMICs). Innovative interventions are needed. We aimed to describe and assess the impact of a community-based psychiatric intervention among PWID in Hai Phong, Vietnam Methods In a cohort study with one year psychiatric follow-up, PWID diagnosed with a psychotic disorder, a major depressive episode, or suicide risk, were recruited from the wider Drug-Related Infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…As a direct consequence of the socioeconomic changes, drug use was also impacted worldwide but the observed changes vary by population, substance use, and geographical location ( Mantell et al, 2021 , Marcus and Snowden, 2020 ). Most countries recorded a decrease in drug use directly related to social distancing ( EMCDDA 2020 , Michel et al, 2022 , Mistler et al, 2021 ). Meanwhile, having more time and boredom were reasons for increased cannabis use according to several cross-sectional online surveys in Australia and Europe ( Marcus and Snowden, 2020 , Mistler et al, 2021 Mar 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a direct consequence of the socioeconomic changes, drug use was also impacted worldwide but the observed changes vary by population, substance use, and geographical location ( Mantell et al, 2021 , Marcus and Snowden, 2020 ). Most countries recorded a decrease in drug use directly related to social distancing ( EMCDDA 2020 , Michel et al, 2022 , Mistler et al, 2021 ). Meanwhile, having more time and boredom were reasons for increased cannabis use according to several cross-sectional online surveys in Australia and Europe ( Marcus and Snowden, 2020 , Mistler et al, 2021 Mar 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, having more time and boredom were reasons for increased cannabis use according to several cross-sectional online surveys in Australia and Europe ( Marcus and Snowden, 2020 , Mistler et al, 2021 Mar 26 ). In particular, the closure of borders by countries affected drug supply, including availability, price, quality of production and opportunities to meet for drug use ( LeSaint and Snyder, 2020 Aug 18 , Michel et al, 2022 , Molès et al, 2020 Apr 24 , Nanda, 2021 ). A study from K. Lindqvist and colleagues conducted in Sweden during COVID-19 epidemic showed that 60% of PWID rather injected heroin alone at home at that time ( Nguyen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Te evidence of community-based HR that supports drug users with mental disorders has been demonstrated in many studies, including the one done in Vietnam [234]. Michel et al [234] reported the prevalence of mental conditions in drug users and suggested that peer support is important to reduce substance use disorders and improve mental health. HR initiative can utilize community-based approaches for psychological support and screening.…”
Section: Community-based Initiatives To Combat Nps and Harm Reduction...mentioning
confidence: 99%
“…Drug users who receive psychiatric care from the community have signifcant improvement in their mental disorders. Michel et al [234] reported that in a year, the rates of suicide risks, depression, and psychotic disorder in afected patients signifcantly reduced from 42.4%, 80.6%, and 44.7%, to 22.9%, 15.9%, and 21.8%, respectively. Similarly, in south eastern part of Nigeria, community-based initiatives were introduced to combat drug abuse [76].…”
Section: Community-based Initiatives To Combat Nps and Harm Reduction...mentioning
confidence: 99%
“…Moreover, hospitalization rates have been reported to range from 35% to 40% among PWID (Palepu et al, 2001;Takahashi et al, 2007). PWID are affected by depressive and psychotic disorders (Michel et al, 2022;Reddon et al, 2018) and/or physical diseases such as HIV infection or hepatitis C, which may result in greater ED use and/or hospitalization (Kendall et al, 2017;Lloyd-Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%